2009
DOI: 10.1016/j.cll.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The Human Bocaviruses: A Review and Discussion of Their Role in Infection

Abstract: Respiratory tract infections are a leading cause of morbidity and mortality worldwide. The human bocavirus (HBoV) is a newly recognized human parvovirus first reported in 2005. Since its discovery, this virus has been associated with upper and lower respiratory tract disease and gastroenteritis worldwide. This article is a comprehensive review of what is known about HBoV. It includes an evaluation of diagnostic modalities, symptoms occurring in affected patients, and a discussion as to whether HBoV is responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
59
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 107 publications
(155 reference statements)
14
59
0
Order By: Relevance
“…Our results was in agreement with Jiang et al, (2016) who reported that the infections almost completely confine to infants and young children also in agreement with most of the previous studies by Allender et al, (2005), Choi et al, (2006), Chow et al, (2009) and Abdel-Moneim et al, (2013). However, some authors reported that HBoV is also a frequent virus in adults with respiratory disease Guido et al, (2012) and Ghietto et al, (2012).…”
Section: Resultssupporting
confidence: 82%
“…Our results was in agreement with Jiang et al, (2016) who reported that the infections almost completely confine to infants and young children also in agreement with most of the previous studies by Allender et al, (2005), Choi et al, (2006), Chow et al, (2009) and Abdel-Moneim et al, (2013). However, some authors reported that HBoV is also a frequent virus in adults with respiratory disease Guido et al, (2012) and Ghietto et al, (2012).…”
Section: Resultssupporting
confidence: 82%
“…HBoV-1 was commonly co-detected with a median rate of 42.5 %, and the most frequent co-detected viruses included rhinovirus, enteroviruses, and influenza [23]. We demonstrated a co-detection rate of 77.72 %, which is similar to the high proportion of co-detection as previously studied [24], yet significantly higher than those from other studies [9,12].…”
Section: Discussionsupporting
confidence: 85%
“…Many studies have been published investigating the role of the virus in respiratory tract illness (6). Some raise the possibility that HBoV is associated with severe respiratory disease (7,8).…”
Section: Case Reportmentioning
confidence: 99%